Attitude and resistance to organizational change in mining workers - Salgado Roa, Jorge Alejandro (2018)
The aim of the study was to analyze the relationship between attitude and resistance to organizational change in mineworkers. An associative transversal strategy of natural groups design was used. The following instruments were administered: the scale of attitudes towards change (EAC), the scale of resistance to change (ERC) and a survey to collect sociodemographic data. 251 workers participated, mostly men. The results indicate a favorable attitude toward organizational change, and a medium/moderate level of resistance. Significant differences in scores of ERC and EAC according to the work task were found. Labor hierarchy generates a modest effect on differences in factors associated with responsibility and the attitude of cynicism to change. With respect to age, workers older than 51 years of age scored lower than the lowest ranks in the dimension of fearful attitude towards change.